Replication-Dependent and Transcription-Dependent Mechanisms of DNA Double-Strand Break Induction by the Topoisomerase 2-Targeting Drug Etoposide - Tammaro, Margaret; Barr, Peri; Ricci, Brett; Yan, Hong (PLOS ONE, 2013)
Etoposide is a DNA topoisomerase 2-targeting drug widely used for the treatment of cancer. The cytoxicity of etoposide correlates with the generation of DNA double-strand breaks (DSBs), but the mechanism of how it induces DSBs in cells is still poorly understood. Catalytically, etoposide inhibits the re-ligation reaction of Top2 after it nicks the two strands of DNA, trapping it in a cleavable complex consisting of two Top2 subunits covalently linked to the 5’ ends of DNA (Top2cc). Top2cc is not directly recognized as a true DSB by cells because the two subunits interact strongly with each other to hold the two ends of DNA together. In this study we have investigated the cellular mechanisms that convert Top2ccs into true DSBs. Our data suggest that there are two mechanisms, one dependent on active replication and the other dependent on proteolysis and transcription. The relative contribution of each mechanism is affected by the concentration of etoposide. We also find that Top2α is the major isoform mediating the replication-dependent mechanism and both Top2α and Top2 mediate the transcription-dependent mechanism. These findings are potentially of great significance to the improvement of etoposide’s efficacy in cancer therapy.